Pengulangan Tindak Pidana oleh Narapidana Pasca Asimilasi dan Integrasi pada Masa Pandemi Covid-19 - Wardah Qurni Nabilah (Faculty of Law, Universitas Airlangga, 2021)
AbstractWith the stipulation of Corona Virus Disease 2019 (Covid-19) as a national disaster through Presidential Decree (Keppres) of the Republic of Indonesia Number 12 of 2020 concerning the Determination of Non-Natural Disaster for the Spread of Corona Virus Disease 2019 (Covid-19) as a National Disaster, Minister of Law and Rights Human Rights conducts one of the efforts to prevent the transmission of covid-19 in prisons, detention centers and special guidance institutions for children by ratifying policies related to assimilation and integration for prisoners and children, this policy is then added to a system of guidance and guidance as well as supervision by the Correctional Center through Supervisors Community services carried out online with the aim that the prisoner does not commit a criminal act again, but this provision is not accompanied by stricter sanctions against inmates who commit repeated crimes, this is evidenced by the increase in criminality which then causes asked in the community regarding the effectiveness of the programKeywords: Assimilation and Integration; Covid-19; Repetition of Criminal Acts.AbstrakDengan ditetapkannya Corona Virus Disease 2019 (Covid-19) sebagai bencana nasional melalui Keputusan Presiden (Keppres) Republik Indonesia Nomor 12 Tahun 2020 tentang Penetapan Bencana Non-Alam Penyebaran Corona Virus Disease 2019 (Covid-19) Menteri Hukum dan Hak Asasi Manusia melakukan salah satu upaya pencegahan penularan covid-19 di lembaga pemasyarakatan, rumah tahanan dan lembaga pembinaan khusus anak dengan mengesahkan kebijakan terkait asimilasi dan integrasi bagi narapidana dan anak, kebijakan tersebut kemudian ditambah dengan sistem pembinaan dan pembimbingan serta pengawasan oleh Balai Pemasyarakatan melalui Pembimbing Kemasyarakatan yang dilakukan secara daring dengan tujuan agar narapidana tidak melakukan perbuatan tindak pidana lagi ,namun ketentuan tersebut tidak dibarengi dengan sanksi yang lebih tegas terhadap narapidana yang melakukan pengulangan tindak pidana, hal tersebut dibuktikan dengan meningkatnya kriminalitas yang kemudian menimbulkan tanya di masyarakat terkait keefektifan program tersebut. Kata Kunci: Asimilasi dan Integrasi; Covid-19; Pengulangan Tindak Pidana.